An aircraft boarding model accounting for passengers’ individual properties - Tang, T.; Wu, Yong Hong; Huang, H.; Caccetta, Louis (Elsevier, 2012)
Aircraft boarding is a very complex process. In this paper, we propose a new aircraft boarding model with consideration of passengers’ individual properties. The model is then applied to explore the dynamic properties of passengers’ motions under three different aircraft boarding strategies including the random boarding strategy, the boarding strategy based on passenger’s seat serial number and individual properties. Our numerical results illustrate that overtaking, queue-jumping, seat conflict congestions and jams may occur under the first two boarding strategies, but these phenomena do not occur under the third boarding strategy. The results indicate that the third boarding strategy is more effective than the other two boarding strategies.